التحول العقدي جذوره وتأثيراته السياسية :زيد بن علي ويحيى بن الحسين أنموذجاً: The Origin of Transformation of ‘Aqidah and Their Impact on Politics: A Study on Zayd bin ‘Alī and Yaḥyā bin al-Ḥusayn - Hassan Alwajeeh, Mohammad Qaed (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
This study highlights the differences of political thought between Zayd bin ‘Alī bin Abi Talib r.a and Yaḥyā bin al-Ḥusayn, founder of Zaydiyyah state in Yemen regarding the doctrine of al-Imamah, al-Wisayah, al-‘Ismah, al-Rajʽah and al-Taqiyyah. Therefore, this article adopts the inductive descriptive historical approach to achieve the objectives of the study. The most significant results shows that Zayd bin ‘Alī denied the Imams’ infallibility, al-Mahdiyyah and rajʽah, al-Wisayah (guardianship), taqiyyah and otherwise acknowledged the legitimacy of the two early caliphs; which makes his madhhab among the most moderate and the closest to the Sunni. In contrast, Yahyā bin al-Ḥusayn linked the concept of imamate to the Prophethood, acknowledged rajʽāh and al-Wisayah as proof of the legitimacy of ‘Ali (radiyallah anh) and his sons as imams. This stand shows an agreement with the Twelver (Shia Ithna ‘Ashariyyah).